Role of green technology, environmental taxes, and green energy towards sustainable environment: Insights from sovereign Nordic countries by CS-ARDL approach - Sharif, Arshian; Kartal, Mustafa Tevfik; Bekun, Festus Victor; Pata, Ugur Korkut; Foon, Chan Ling; Depren, Serpil Kilic (ELSEVIER, 2023)
This study analyzes comprehensively the role of green technology, environmental taxes, and green energy toward a sustainable environment in 5 sovereign Nordic countries by also considering income and population. For this purpose, annual data of Nordic countries from 1995 to 2020 is extracted and the cross-sectional augmented autoregressive distributed lag (CS-ARDL) technique is applied to test short-run and long-run compatibilities of the indicators on carbon dioxide (CO2) emissions. Moreover, Augmented Mean Group (AMG) and Common Correlated Effects Mean Group (CCEMG) approaches are applied for robustness checks. The empirical results reveal that (i) green technology, environmental taxes, and green energy have a negative association with CO2 emissions in the both short-run and long-run; (ii) income and population have a positive association between CO2 emissions in the both short-run and long-run; (iii) AMG and CCEMG approaches report similar findings with the CS-ARDL and validate the robustness in turn. Thus, the empirical results confirm the contributing role of green technology, environmental taxes, and green energy toward a sustainable environment in 5 sovereign Nordic countries. Moreover, policy implications are discussed.(c) 2023 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Green Technology; Environmental Taxes; Green Energy; CO2; Nordic Countries; UNIT-ROOT TESTS; CONSUMPTION; PANELS; DEPENDENCE; EMISSIONS; INFERENCE; GROWTH; MATTER; WEAK; Geology